INFLUENCE OF PLANNING, MANAGEMENT, MONITORING AND EVALUATION OF REVENUE AND EXPENDITURE BUDGET ON THE FINANCIAL PERFORMANCE OF REGIONAL PUBLIC SERVICE AGENCIES BALANGAN REGIONAL PUBLIC HOSPITAL - Devvie Lies Indrawati; Noor Ritawaty (INFOKUM, 2022)
This study aims to describe the financial performance of the Regional Public Service Agency of the Balangan Regional General Hospital using independent variables consisting of Financial Planning (X1), Financial Management (X2) Monitoring Evaluation (X3) and the dependent variable, namely Financial Performance (Y). This study uses a quantitative approach, which is a method used to answer problems and emphasize numerical research that focuses on the results of data processing in the form of numbers and statistical programs to find new facts to prove a theory. Qualitative research is carried out to build knowledge through understanding and discovery. The results of all variables indicate that there is a significant effect of the functions of financial planning (X1), financial management (X2), monitoring and evaluation (X3) on financial performance (Y) at the Balangan District Hospital simultaneously, while partially not having a significant effect. In this study, the more dominant variable in influencing financial performance is financial management (X2).